Temperature and carbon dioxide elevation effects on yield and quality of groundnut haulms as livestock feed - Damarla Bala Venkata Ramana; Maddi Vanaja; Mathukumalli Srinivasa Rao; Juleri Maruti Upendra; Poldasari Sathish; Mathyam Prabhakar; Vinod Kumar Singh; Jagadish Timsina (Journal of Agriculture and Food Research)
Groundnut (Arachis hypogaea L.) is a major legume crop in India and faces challenges due to changing climate conditions. The objective of this study was to assess the impact of elevated temperature (eT, 3.0 ± 0.5 °C above ambient) and its interaction with elevated carbon dioxide (eCO2, 550 ± 50 ppm) on yield and nutritional quality of haulms from groundnut crop. The experiment was conducted with two groundnut varieties (K6 and Narayani) and was evaluated under ambient temperature + ambient carbon dioxide (A), elevated temperature + ambient carbon dioxide (eT) and elevated temperature + elevated carbon dioxide (eT + eCO2) conditions of free air temperature elevation (FATE) facility. Elevated temperature significantly reduced the yield of haulms compared to ambient conditions. Elevated CO2 concentrations compensated to a major extent for temperature-induced yield reductions. Nutrient content in haulms was influenced by environmental conditions, with higher ash and lower organic matter in GN haulms under eT and eT + eCO2 conditions. Elevated temperature and CO2 levels led to decreased crude protein and increased NDF. Calcium increased, whereas phosphorus and zinc content were decreased in haulms under eT and eT + eCO2. Anti-nutritional constituents such as lignin and silica increased under elevated temperature and eCO2 levels. Degradability and energy levels were adversely affected by elevated temperature, with lower total digestible nutrients and in vitro true degradability. In vitro gas production was also decreased under elevated temperature conditions from GN haulms. These findings highlight the complex interactions between climate factors and groundnut haulms as livestock feed, with implications for livestock productivity in the face of future climate change.